The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4244/eijv12i5a99
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic complexity of coronary artery disease according to SYNTAX score and clinical outcomes after revascularisation with newer-generation drug-eluting stents: a substudy of the BIOSCIENCE trial

Abstract: Aims: We sought to assess the performance of drug-eluting stents combining an ultrathin cobalt-chromium platform with a biodegradable polymer across categories of increasing SYNTAX score (SS). Methods and results:Patients included in the BIOSCIENCE trial and randomly allocated to treatment with biodegradable polymer sirolimus-eluting stents (BP-SES) or durable polymer everolimus-eluting stents (DP-EES) were categorised according to SS tertiles (low <8, medium 8-15, high >15). The primary endpoint, target lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…13,30,31 A sub analysis of the BIOSCIENCE trial using SESs showed 2-year rates of death, MI, or repeat revascularization of 14.5% in patients with SYNTAX score > 15 compared to 8.1% and 5.9% in two lower SYNTAX score comparators. 32 demonstrated the superiority of DES over BMS in de novo coronary disease with our data supporting similar findings in radiation induced coronary disease. [34][35][36] Few however have found an association with CV mortality.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…13,30,31 A sub analysis of the BIOSCIENCE trial using SESs showed 2-year rates of death, MI, or repeat revascularization of 14.5% in patients with SYNTAX score > 15 compared to 8.1% and 5.9% in two lower SYNTAX score comparators. 32 demonstrated the superiority of DES over BMS in de novo coronary disease with our data supporting similar findings in radiation induced coronary disease. [34][35][36] Few however have found an association with CV mortality.…”
Section: Discussionsupporting
confidence: 87%
“…Though the median score of 11 represents a relatively low SYNTAX score, worse outcomes with increasing score suggest XRT‐CAD shares similarities to de novo coronary disease consistent with the original derivation and validation of SYNTAX . A sub analysis of the BIOSCIENCE trial using SESs showed 2‐year rates of death, MI, or repeat revascularization of 14.5% in patients with SYNTAX score > 15 compared to 8.1% and 5.9% in two lower SYNTAX score comparators . Garg et al used SYNTAX score to compare results of the patients undergoing PCI with newer generation zotarolimus‐ or everolimus‐eluting stents in the RESOLUTE III Trial and found increased rates of a composite endpoint in patients with SS ≥ 17 compared with SS ≤ 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In our current analysis, the number of uncovered scaffold struts in the (very) late ScT cases are comparable with the observed number of uncovered metallic stent strut. However, the number of malapposed struts seems to be higher in Absorb (6.0%) as in metallic stents (1.3%) .…”
Section: Discussionmentioning
confidence: 84%
“…Recently, the Synergy Between PCI With Taxus and CABG (SYNTAX) score was developed. [10] It is a tool which takes into consideration the anatomical features of the coronary lesions as a guide to assess patients who will be eligible for PCI. [11] …”
Section: Introductionmentioning
confidence: 99%